The Influence of Material Mastery on Pre-service Teachers’ Teaching Readiness in Teaching Assistance of Freedom to Learn-Independent Campus Program - Riki Maryo; Achmadi Achmadi; Muhammad Basri (International Journal of Learning and Instruction (IJLI), 2023)
This study aimed to analyze the effect of material mastery on the pre-service teachers’ teaching readiness of Freedom to Learn-Independent Campus (MBKM) in teaching assistance of the economic education study program at Universitas Tanjungpura. The background of this study was many pre-service teachers in economics education study programs still experience unpreparedness in carrying out learning activities in class while participating in teaching assistance. This study used a quantitative approach with a causal method. The study population consisted of 90 pre-service teachers with a sample of 50 pre-service teachers and used a simple random sampling technique. The results showed that material mastery did not affect the readiness to teach in the teaching assistance of the MBKM program in the economics education study program, with a significance value of 0.587 > 0.05. Based on the results of this study, it can be concluded that mastery of the material does not affect the readiness to teach for pre-service teachers in teaching assistance of the MBKM program. Keywords: Material Mastery, Teaching Readiness, MBKM Teaching Assistance